Estimation of ventricles size of human brain by Magnetic Resonance Imaging in Nepalese Population: A retrospective study - Sushma Singh; Bhoj Raj Sharma; Urusha Prajapati; Pujan Sharma; Manoj Bhatta; Nawaraj Paudel (Journal of Gandaki Medical College, 2020)
Background and Objective: Magnetic resonance imaging (MRI) provides image acquisition of three-dimensional data and measurement in any chosen imaging plane. Objective of this study is to assess the size of ventricles of the brain of normal Nepalese people and establish the range of size of the ventricular system and compute the ventricular dimensions among different age and gender.